(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
Under Regulation 207/2009 / EC, a licensee which is not registered in a suitable register cannot initiate proceedings due to a violation of trademark rights. The subject of this analysis is how the courts in the Member States of the European Union are acting on this issue, i.e. how they apply Article 23 paragraph 1 of Regulation 207/2009 / EC. Firstly, authors are analysing the issue concerning the rights of the licensee which has not been registered in an appropriate register has in the event of a violation of a trademark right. The authors endeavour to reexamine the uniqueness of acting in practice in a way that would encircle a research process and would see flaws in the normative regulation of the same. Considering that in practice there are cases in which, according to Article 23, paragraph 1 of the Regulation, the courts in the Member States of the European Union adopt different judgement, the case of the analyse is the judgment of the European Court of Justice C-163/15. The aim of this paper is to point out that only through an efficient system of protection and proper implementation of the legislation, taking into account the practice of the European Court of Justice will contribute to the stabilization of the economic circulation of goods and services.